Evaluation of the properties of the canola cake in automated extruder press extraction process by varying temperature and rotation (Research, Society and Development, 2021)
Oil crops are important in the Brazilian agricultural sector, both for food production (grains, oil, and bran), pharmaceuticals and biofuels. One of the criteria for the improvement of technologies to develop products with superior quality and added value has been through the nutritional parameter. In this way, it is important to improve the continuous mechanical pressing process in order to obtain the optimum temperature point and extraction rotation to provide higher nutritional quality of the oil and the canola cake. In view of the above, the objective of the study was to evaluate the process of mechanical pressing of canola grains at different temperatures and rotational speeds in a mechanical extruder with automation over bromatological characteristics, color (DE). As well as evaluate pie moisture, raw fiber, ethereal extract, protein, carbohydrates, and fixed mineral residue. The study was developed in factor scheme 4 5, being 4 temperatures (110-120, 120-130, 130-140 and 140-150 °C) and 5 speeds (1000, 1200, 1400, 1600 and 1800 rpm). The coefficient (R2) was determined as a statistical parameter in which the maximum values in percentage of pie moisture, crude fiber, ethereal extract, protein, carbohydrates, and fixed mineral residue were, respectively, 9.19; 17.19; 32.66; 35.90; 27.29 and 7.32%. By the color of the canola pie, it was noticeable that the darker coloring of the pie presented high percentage of protein, and the lighter colors, high percentage of ethereal extract.